Suitability analysis for extrusion-based additive manufacturing process - Altıparmak, S. C.; Daminabo, Samuel I. Clinton (Elsevier, 2024)
Additive manufacturing (AM) is a widely applied manufacturing paradigm used for the layer-by-layer fabrication of desired components and objects, especially for those with highly intricate geometry. Extrusion-based AM, which is a subcategory of AM processing technologies, is characterized by the facilitation of controlled and successive deposition of feedstock AM materials through the nozzles of printer heads onto a print bed. Extrusion-based AM processing enables design freedom but offers cost efficiency and process simplicity when compared to other AM categories i.e. liquid- and powder-based AM technologies. The extrusion-based AM process has become increasingly widespread over the last two decades because of the expanding material options that can be used in this technology, and its capacity to be hybridised through the addition of multiple printheads or incorporation into a secondary manufacturing system. Despite the promising aspects of the extrusion-based AM process, increasing demands for customised extrusion-based printed products and an expanding range of extrusion-based AM materials create both material- and process-related challenges that limit the suitability of extrusion-based AM processes for some specific applications. Consequently, the principal objective of this review paper is to conduct a suitability analysis of extrusion-based AM processes. The suitability analysis follows a review and discussion about the extrusion-based AM process, and an assessment of easy- and hard-to-print extrusion-based AM materials. This paper, therefore, provides a comprehensive suitability analysis of each extrusion-based AM process while also providing some promising ideas for improving their current suitability levels. The findings and ratings reported in this paper importantly offers viewpoints that would support better futuristic comparisons between developed and developing extrusion-based AM processes, especially as businesses look to adopt the right AM solutions.
Keywords: Extrusion-based additive manufacturing; Suitability analysis; Additive manufacturing materials; 3D printing